Sharia hotel management strategies for Halal tourism competitiveness in Padang Lawas, North Sumatra, Indonesia - Harahap, Rijal Allamah; Harahap, Haddad 'Ulum (Journal of Islamic Economics Lariba, 2026)
IntroductionSharia-compliant hotels play an important role in supporting the development of halal tourism in Indonesia. However, their competitiveness remains challenged by conventional hotels that increasingly provide halal-friendly services, especially in regional destinations outside major tourism centers. In Padang Lawas Regency, North Sumatra, Sharia hotel management faces complex issues related to weak differentiation, limited facilities, uneven implementation of Islamic principles, underdeveloped human resource professionalism, and suboptimal digital marketing.ObjectivesThis study aims to analyze the management strategies of Sharia-compliant hotels in facing competition within the halal tourism industry from an Islamic economic perspective. It specifically examines marketing strategy, operational management, human resource management, digital marketing, and the implementation of maqāṣid al-sharī‘ah in hotel management.MethodThis study used a descriptive qualitative approach. Data were collected through semi-structured interviews, direct observation, and hotel documentation involving managers, key staff, and supporting personnel of Sharia-compliant hotels in Padang Lawas Regency, North Sumatra, Indonesia. The data were analyzed using the interactive model of data reduction, data display, and conclusion drawing. Data validity was strengthened through source triangulation, technique triangulation, and member checking.ResultsThe findings show that Sharia-compliant hotels have implemented Islamic values through halal food, prayer facilities, modest service norms, ethical communication, and guest regulations. However, these practices have not yet developed into an integrated competitive strategy. Marketing remains largely conventional, operational standards are inconsistent, human resource development is still informal, and digital marketing is not yet used strategically to strengthen halal brand image and consumer trust. The implementation of maqāṣid al-sharī‘ah is visible in basic religious service attributes but remains limited in broader dimensions such as employee welfare, business sustainability, transparent governance, and community benefit.ImplicationsThis study indicates that the competitiveness of Sharia-compliant hotels requires substantive differentiation, credible Sharia governance, professional human resources, stronger digital visibility, and maqāṣid-oriented management. Regional halal tourism development also requires collaboration among hotel managers, local government, religious authorities, communities, and digital platforms.Originality/NoveltyThis study contributes to halal tourism and Islamic economics literature by integrating strategic management, Islamic marketing, human resource management, digital marketing, Sharia governance, and maqāṣid al-sharī‘ah into one analytical framework for Sharia hotel competitiveness in a regional Indonesian context.